Impressive Result of Gemcitabine and Cisplatin Combination Therapy in Post-Operative Residual Cholangiocarcinoma Patient Presenting with Hyperbilirubinemia, an Experience in Indonesian Tertiary Hospital - Ibnu Purwanto; Agus Barmawi; Bambang Purwanto Utomo; Ahmad Ghozali (Acta Interna The Journal of Internal Medicine, 2020)
Introduction: Cholangiocarcinoma (CCA) often presents at an inoperable or an advanced stage in which complete resection is not possible. In such scenario, chemotherapy often is the only option to improve patient’s survival. Severe hyperbilirubinemia, often associated with higher risk of developing chemotherapy-related adverse event, might complicates one’s decision in choosing chemotherapy regimen. Case Report: We present a case of 63-year-old post-operative CCA patient with residual mass and severe hyperbilirubinemia. The patient completed six cycles of gemcitabine (1000 mg/m2, day 1 and 8) and cisplatin (70 mg/m2, day 1) every 3 weeks with tolerable side effect. No sign of residual tumor was observed on CT-Scan performed one-month post chemotherapy. Conclusion: Combination of cisplatin and gemcitabine may offer safe treatment option for post-operative residual CCA patient presenting with hyperbilirubinemia.